2019
DOI: 10.1007/s10948-019-05386-0
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Crystal Field Potential by Orbital Dilution in Strongly Correlated d4 Oxides

Abstract: We investigate the interplay between Coulomb driven orbital order and octahedral distortions in strongly correlated Mott insulators due to orbital dilution, i.e., doping by metal ions without an orbital degree of freedom. In particular, we focus on layered transition metal oxides and study the effective spin-orbital exchange due to d 3 substitution at d 4 sites. The structure of the d 3 −d 4 spin-orbital coupling between the impurity and the host in the presence of octahedral rotations favors a distinct type o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Hideo Aoki [92] This is a typical scenario near a Lifshitz transition for the appearing of a new Fermi surface spot described for organics [86] and predicted also for pressurized sulfur hydrides [93][94][95]. Advances on quantum mechanics of orbital physics which is today a hot topic have been obtained by Oleś group showing orbital dilution in d 4 oxides by tuning crystal field potential [96] and magnetic properties of crystalline and ferroelectric layered rare-earth-titanate by Kuznetsov et al [97]. Strain Induced orbital dynamics across the metal insulator transition in thin VO 2 films [98] provide further information on nanoscale phase separation in the correlation-driven insulator-metal transition in vanadium dioxide [99][100][101][102].…”
Section: The Superstripes 2019 Conferencementioning
confidence: 92%
“…Hideo Aoki [92] This is a typical scenario near a Lifshitz transition for the appearing of a new Fermi surface spot described for organics [86] and predicted also for pressurized sulfur hydrides [93][94][95]. Advances on quantum mechanics of orbital physics which is today a hot topic have been obtained by Oleś group showing orbital dilution in d 4 oxides by tuning crystal field potential [96] and magnetic properties of crystalline and ferroelectric layered rare-earth-titanate by Kuznetsov et al [97]. Strain Induced orbital dynamics across the metal insulator transition in thin VO 2 films [98] provide further information on nanoscale phase separation in the correlation-driven insulator-metal transition in vanadium dioxide [99][100][101][102].…”
Section: The Superstripes 2019 Conferencementioning
confidence: 92%
“…Doping with Mn impurities leads to substitution of with configurations, having local S = 3/2 and without an orbital degree of freedom (doublon). It has been recently demonstrated that the spin–orbital exchange driven by Coulomb correlations yields an orbital reconstruction around the impurity sites 24 , 25 . In particular it acts as an effective crystal field potential , which tends to promote the doublon to the ( , ) sector (see Fig.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…The existence of the mixing Cr 3+ /Cr 4+ states in the octahedral oxygen co-ordinations of CuCrO 2 delafossite caused strong correlation for the orbitals and the spin degeneracy of the charge carriers as a result of the crystal field. 20 This influenced the thermopower property of the CuCrO 2 material. The transition delafossite oxide compounds formed a phase in the preparation temperature of 1000-1100 • C. 21 The specific significance of the mixed valence transition CuCrO 2 was applied in data storage, temperature sensors, thermoelectric, p-type transparent conducting devices, dye-sensitized solar cells, photoelectrodes, energy storage, and electrode for lithium-ion batteries.…”
Section: Introductionmentioning
confidence: 99%